Warfighting and disruptive technologies : disguising innovation - Pierce, Terry C. (Cass series--strategy and history., 2004)
Occasionally, during times of peace, military forces achieve major warfighting innovations. Terry Pierce terms these developments 'disruptive innovations' and shows how senior leaders have often disguised them in order to ensure their innovations survived. He shows how more common innovations however, have been those of integrating new technologies to help perform existing missions better and not change them radically. The author calls these 'sustaining innovations'. The recent innovation history suggests two interesting questions. First, how can senior military leaders achieve a dis.